Consumer Preferences for Electric Vehicle in Kathmandu - Pokhrel, Anish; Pradhan, Sumit (Nepalese Journal of Business, 2025)
This study examines the consumer preferences for electric vehicles in Kathmandu. Consumer preferences are the dependent variable. The selected independent variables are financial attributes, technical attributes, charging availability, social influence, and environment concern. The primary sources of data are used to assess the opinions of respondents regarding financial attributes, technical attributes, charging availability, social influence, and environment concern. The study is based on the primary data of 128 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the Consumer preferences for electric vehicle in Kathmandu. The study showed that financial attributes is positively correlated with consumer preferences for electric vehicles, it means that financial attributes influence consumer preference for electric vehicles. Likewise, technical attributes is positively correlated with consumer preference for electric vehicles, it means that technical attributes influence consumer preferences for electric vehicles. Similarly, charging availability is positively correlated with consumer preferences for electric vehicles, it means that charging availability influence consumer preference for electric vehicles. Likewise, social influence is positively correlated with consumer preference for electric vehicles, it means that social influence consumer preference for electric vehicle. Moreover, environment concern is positively correlated consumer preference for electric vehicle it means that environment concern influence consumer preference for electric vehicles.